Pengaruh E-Service Quality terhadap Minat Beli Ulang dengan Kepuasan Pelanggan Sebagai Variabel Intervening pada Marketplace Shopee - Nellvian Nita; Ina Ratnasari (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to examine and analyze the Effect of E-Service Quality on Repurchase Interest with Customer Satisfaction as an Intervening Variable in the Shopee Marketplace. This study uses primary data obtained from the results of distributing questionnaires to Shopee Instagram followers. The method used is quantitative with a descriptive and verification approach. The sample in this study was 400 samples from 8,489,846 populations taken using nonprobability sampling method with purposive sampling technique. The data analysis used is path analysis with partial hypothesis testing and mediation/sobel tests. The results of the study show that E-Service Quality has a positive and significant effect on customer satisfaction in the Shopee marketplace. E-Service Quality has a positive and significant effect on Repurchase Interest in the Shopee marketplace. Customer Satisfaction has a positive and significant effect on Repurchase Interest in the Shopee marketplace. There is an indirect influence between E-Service Quality on Repurchase Interest through Customer Satisfaction on the Shopee marketplace.